2011
DOI: 10.1029/2010pa002053
|View full text |Cite
|
Sign up to set email alerts
|

Multiple‐stage deglacial retreat of the southern Greenland Ice Sheet linked with Irminger Current warm water transport

Abstract: There is limited knowledge pertaining to the history of the Greenland Ice Sheet (GIS) during the last glacial‐interglacial transition as it retreated from the continental margins to an inland position. Here we use multiproxy data, including ice‐rafted debris (IRD); planktonic isotopes; alkenone temperatures; and tephra geochemistry from the northern Labrador Sea, off southwest Greenland, to investigate the deglacial response of the GIS and evaluate its implications for the North Atlantic deglacial development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 151 publications
3
47
0
Order By: Relevance
“…However, distal freshwater release farther north, such as from Greenland, cannot be excluded. In the northmost Labrador Sea, Knutz et al (2011) observed two pulses of large oxygen isotope depletions with increased ice-rafted detritus before Younger Dryas event from Core DA04-31P within West Greenland Current (Fig. 7).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, distal freshwater release farther north, such as from Greenland, cannot be excluded. In the northmost Labrador Sea, Knutz et al (2011) observed two pulses of large oxygen isotope depletions with increased ice-rafted detritus before Younger Dryas event from Core DA04-31P within West Greenland Current (Fig. 7).…”
Section: Discussionmentioning
confidence: 90%
“…The meltwater trapped by the West Greenland Current might be also Rashid et al (2003). IRD abundance in core DA04-31P is redrawn from Knutz et al (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as changing ocean currents (e.g. Knutz et al, 2011;Winsor et al, 2012) and internal ice-sheet dynamics (e.g. Joughin et al, 2001) may have played an important role for the difference in timing of initial ice-margin retreat between regions.…”
Section: Last Glacial Maximum Ice Extent and Timing Of Initial Retreatmentioning
confidence: 99%
“…Greenland Current system has been reported in the north eastern Labrador Sea during the last deglacial period by Knutz et al (2011).…”
Section: Sst Variability Offshore Southeast Greenlandmentioning
confidence: 99%